Potent, Plasmodium-Selective Farnesyltransferase Inhibitors That Arrest the Growth of Malaria Parasites: Structure—Activity Relationships of Ethylenediamine-Analogue Scaffolds and Homology Model Validation - Fletcher, Steven (2008)
New chemotherapeutics are urgently needed to combat malaria. We previously reported on a novel series of antimalarial, ethylenediamine-based inhibitors of protein farnesyltransferase (PFT). In the current study, we designed and synthesized a series of second generation inhibitors, wherein the core ethylenediamine scaffold was varied in order to examine both the homology model of Plasmodium falciparum PFT (PfPFT) and our predicted inhibitor binding mode. We identified several PfPFT inhibitors (PfPFTIs) that are selective for PfPFT versus the mammalian isoform of the enzyme (up to 136-fold selectivity), that inhibit the malarial enzyme with IC(50) values down to 1 nM, and that block the growth of P. falciparum in infected whole cells (erythrocytes) with ED(50) values down to 55 nM. The structure–activity data for these second generation, ethylenediamine-inspired PFT inhibitors were rationalized by consideration of the X-ray crystal structure of mammalian PFT and the homology model of the malarial enzyme.